Gatekeeping as Leverage: Morocco Strategic Agency in European Union Migration Management - ElKady, Nadine Omar (AUC Knowledge Fountain, 2026)
This thesis examines how Morocco has leveraged migration as an instrument in its relation with the European Union (EU). Following the Arab Spring, Morocco has utilized this opportunity to implement its own agenda and bargain with the EU on prevention tactics for irregular migration. I argue that cooperation for migration management between the EU and Morocco is built on bargaining processes and tactics from Morocco, which has shifted power dynamics from being merely a passive actor to a key player. Morocco's cooperation reflects calculated bargaining strategies rather than a response to the EU pressure. The research utilizes qualitative methodology, combining document analysis of Morocco’s agreements with the EU and documents from international organizations. By using process tracing to map causal linkages, Morocco’s tactical cooperation and the EU concessions are examined. In addition, the research employs rationalist theory to track Morocco’s cost benefit analysis and strategic interdependence, as well as its ability to exploit asymmetrical power dynamics, transforming migration from a policy challenge into a diplomatic asset.